Respostas

2014-05-21T21:28:44-03:00
(a11  a12  a13  a14)
(a21  a22  a23  a24)
(a31  a32  a33  a34)

aij = 2i-3j
a11 = 2.1-3.1 = 2 - 3= -1
a12 = 2.1-3.2 = 2 - 6 = -4
a13 = 2.1-3.3 = 2 - 9 = -7
a14 = 2.1-3.4 = 2 - 12 = -10
a21 = 2.2-3.1 = 4 - 3 = 1
a22 = 2.2-3.2 = 4 - 6 = -2
a23 = 2.2-3.3 = 4 - 9 = -5
a24 = 2.2-3.4 = 4 - 12 = -8
a31 = 2.3-3.1 = 6 - 3 = 3
a32 = 2.3-3.2 = 6 - 6 = 0
a33 = 2.3-3.3 = 6 - 9 = -3
a34 = 2.3-3.4 = 6 - 12 = -6

(-1  -4  -7  -10)
(1   -2  -5    -8) 
(3    0  -3    -6)
2 5 2